Penatalaksanaan Fisioterapi Pada Kasus Bronkopneumonia Pada Anak - Dini Nur Alpiah; Muhammad Ilham Maulana; Djenar Ayu Hanifah; Salsabila Fatihah; Arzeti Felyanti; Aliya Dwi Latifa; Danu Firmansyah; Shabana Zarra Azmi (Jurnal Ners, 2026)
Bronchopneumonia is a lower respiratory tract infection that remains a cause of morbidity and mortality among children. The condition is characterized by pulmonary inflammation leading to increased secretion production, impaired ventilation, shortness of breath, and reduced respiratory function. This study aimed to determine the effectiveness of a physiotherapy regimen combining chest physiotherapy and infrared therapy for children with bronchopneumonia. A descriptive case study design was employed, involving two female patients—aged 3 years 9 months and 3 years 2 months—diagnosed with bronchopneumonia at Dr. M. Goenawan Partowidigdo Pulmonary Hospital. Assessments conducted before and after the intervention included respiratory rate (RR), the Borg Scale, thoracic expansion, percussion, and auscultation. Physiotherapy interventions—comprising postural drainage, clapping, vibration, infrared therapy, and thoracic cage mobilization—were administered over four days, tailored to each patient's condition and tolerance. The results showed improvements in both subjects, including a decrease in respiratory rate, a reduction in the severity of shortness of breath (based on the Borg Scale), increased thoracic expansion, a shift in percussion sounds from dull to resonant, and a change in auscultation findings from moist rales to vesicular breath sounds. Additionally, the patients demonstrated an improved ability to clear secretions, resulting in cleaner airways. Based on these findings, it can be concluded that the combination of chest physiotherapy and infrared therapy is effective as an adjunctive treatment for clearing airways, enhancing pulmonary ventilation, and improving respiratory function in children with bronchopneumonia.